The Surprise Box Learning Media on Human Reproductive System Material - Rukman, Radhiyah (Side: Scientific Development Journal, 2024)
This research discusses the influence of surprise box learning media on student learning outcomes regarding the human reproductive system in class IX MTsN 3 Enrekang. The type of research used is Quasi Experimental using the Nonequivalent-control Design. The population of this study included all students in class IX MTsN 3 Enrekang totaling 132 students. The sample used was two classes, namely class IX C with 20 people as the experimental class and class IX D with 20 people as the control class. Sampling technique utilized random sampling techniques, where the total number in the sample class was 40 people. The instruments used are tests, learning observation sheets, and documentation. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis that employing normality tests, homogeneity tests and hypothesis tests. The results showed that the average student learning outcome score was 90.25 (very good category) in the experimental class and 67.50 (good category) in the control class. The significance value was 0.000<0.05. Apparently, there is an influence of the use of surprise box learning media on student learning outcomes regarding the human reproductive system in class IX MTsN 3 Enrekang. The research implies that surprise box media can improve learning outcomes and student understanding in learning activities.